Pengembangan Multimedia Interaktif Pada Pembelajaran Tematik Tema Organ Gerak Hewan dan Manusia di Kelas V Sekolah Dasar - Utami, Ajeng Putri; Satria, Tio Gusti; Febriandi, Riduan (Universitas Negeri Padang, 2021)
This research study aims to develop an audio and visual learning media product in the form of Interactive Multimedia in the Thematic Learning of Animal and Human Movement Organs Themes Class V SD Which is valid and practical to use in the learning process. The research method is R&D (Research and Development), with a 4-D development model that only uses 3 stages, namely definition, design and development. Based on the results of the assessment analysis obtained from the language, material and media validators, an average score of 0.78 was obtained with a fairly high description that met the valid criteria. Then the results of the practical analysis of students and teachers obtained an average score of 92% which met the very practical criteria so that it can be concluded that Interactive Multimedia In Thematic Learning of Animal and Human Movement Organ Themes Class V is valid and practical to use in the learning process.